2021
DOI: 10.1038/s41394-020-00371-5
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory morbidity and mortality of traumatic cervical spinal cord injury at a level I trauma center in India

Abstract: Study design Descriptive retrospective. Objectives To evaluate the burden of respiratory morbidity in terms of ventilator dependence (VD) days and length of stay in neurotrauma ICU (NICU) and hospital, and to determine mortality in patients with traumatic cervical spinal cord injury (CSCI) in a low middle-income country (LMIC). Setting Jai Prakash Narayan Apex Trauma Center (JPNATC), All India Institute of Medical Sciences (AIIMS), New Delhi,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Sengupta D et al [54] showed in their descriptive retrospective study that in patients with cervical spinal cord injury in low-middle-income countries (LMIC), ventilation exposure, hospitalization, and mortality are high and the main cause of mortality among them is due to poor AIS values, extended VD, intensive care and hospital stays, comprehensive CSCI rehabilitation programs are required to overcome this situation.…”
Section: Indian Epidemiological Datamentioning
confidence: 99%
“…Sengupta D et al [54] showed in their descriptive retrospective study that in patients with cervical spinal cord injury in low-middle-income countries (LMIC), ventilation exposure, hospitalization, and mortality are high and the main cause of mortality among them is due to poor AIS values, extended VD, intensive care and hospital stays, comprehensive CSCI rehabilitation programs are required to overcome this situation.…”
Section: Indian Epidemiological Datamentioning
confidence: 99%
“…Acute traumatic spinal cord injury (SCI) affects approximately 54 people per million in the United States per year, which equates to 18,000 new cases of SCI yearly. Although not the most common type of acute neurotrauma, it has a high rate of long-term disability and an increase in mortality risk of 2–5 times with the highest risk of death occurring in the first year [ 1 , 2 , 3 ]. Risk factors associated with mortality from SCI include the level of injury, tetraplegia, older age, polytrauma, mechanical ventilation, tracheostomy, septicemia, respiratory complications, and cardiovascular complications [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%